Building a framework to understand and address vulnerability to reading difficulties among children in schools in the United States. Issue 183 (7th July 2022) - Terry, Nicole Patton; Gerido, Lynette Hammond; Norris, Cynthia U.; Johnson, Lakeisha; Little, Callie
Abstract: This paper presents a vulnerability framework as a means to contextualize inequities in reading achievement among children who are vulnerable to poor reading outcomes. Models to understand vulnerability have been applied in the social sciences and public health to identify population disparities and design interventions to improve outcomes. Vulnerability is multifaceted and governed by context. Using a vulnerability framework for the science of reading provides an innovative approach for acknowledging multilevel factors contributing to disparities. The ecological considerations of both individual differences in learners and conditions within and outside of schools ensures that scientific advances are realized for learners who are more vulnerable to experiencing reading difficulty in school.